Zmiany w działalności marketingowej powszechnych towarzystw emerytalnych - Prudzienica-Grunt, Maja (The changes of the marketing activity of the general pension societies, 2006)
The main aim of this article is to find an answer to the question if the changes in the activity of General Pension Societies are driven by market conditions particularly specific for this kind of institutions comparing to other kind of institutions functioning on the capital market (i.e. banks, life insurance societies)? Or are they driven by the series of various circumstances being random from their nature? Once the origin, influence and duration of those changes are identified the answer for the above questions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 272-279